Analisis Faktor-Faktor Store Atmosphere Terhadap Impulse Buying Pada The Warong Distorsi Di Tenggarong - Juwita Andriani; Awang Yacoub Luthman; Ilham Ilham (JEMI is managed and published by the Management Study Program, Faculty of Economics and Business, Kutai Kartanegara University. Institutional legality is reflected in the ISSN number: 1411-9560 published by LIPI in 2003 as a manifestation of the comm, 2019)
Abstract:The purpose of this study was to determine and analyze the influence of store atmosphere factors on impulse buying. The data used is primary data. This research method uses sampling aksidental. Samples were examined as many as 122 respondents. The number of independent variables studied were 4 namely exterior (exterior), general interior (inside), store layout (store layout), interior display (in store display), and with 1 dependent variable namely impulse buying (unexpected purchase) . In this study using an analytical tool, Factor Analysis. From the results of this study states that the first hypothesis in this study which states that "Store Atmosphere Factors consisting of exterior, general interior, store layout and interior display simultaneously have a significant effect on impulse buying" is accepted. This is confirmed by the results seen in the KMO and Bartlett's test tables obtained KMO and Bartlett's test numbers are 0.736 with a significant 0,000. Because the number is above 0.5 and far significant below 0.005 (0,000 <0,005), then the variables and samples that exist can actually be analyzed further. Paying attention to these results provides the basis that what underlies impulse buying at cafe The Warong Distorsi in Tenggarong through visitors' views through 4 factors: exterior, general interior, store layout, interior display has a simultaneous significant influence on impulse buying at Cafe The Warong Distorsi. Then the statement from the second hypothesis which stated that "the most influential general interior of impulse buying at The Warong Distorsi Tenggarong" was accepted. It is proven by the results of component matrix analysis that it can be known through 1 forming component and arranged in rank order, and it can be explained that the exterior factor has a correlation value of 0.789, the general interior gets a value of 0.845, the store layout is 0.826 and the interior display has a value of 0.695. From these results it can be seen that the general interior with the highest value is the most influential variable on impulse buying at The Warong Distorsi.Keywords : Store Atmosphere, Exterior, General Interior, Store Layout, Interior Display, Impulse Buying